PENYELESAIAN NUMERIK MODEL PREDATOR-PREY DENGAN SKEMA BEDA HINGGA TAK-STANDAR - Rina Reorita; Renny Renny (Journal of Fundamental Mathematics and Applications (JFMA), 2019)
Interaction between predator and prey can be represented as a system of non-linear differential equation which is difficult to be solved analytically. In this research, a predator-prey model with an addition of harvesting factor is discretized into a system of difference equation using non-standard finite difference scheme. The analysis result shows that the developed scheme has qualitative property which is consistent to the continuous system.